CREG1 improves diet‐induced obesity via uncoupling protein 1‐dependent manner in mice. (24th January 2022) - Endo, Yuki; Hashimoto, Michihiro; Kusudo, Tatsuya; Okada, Tadashi; Takeuchi, Tamaki; Goto, Ayumi; Yamashita, Hitoshi
Abstract: Thermogenic brown and beige adipocytes express uncoupling protein 1 (UCP1) and stimulate energy metabolism, protecting against obesity and metabolic diseases such as type 2 diabetes and hyperlipidemia. Cellular repressor of E1A‐stimulated genes 1 (CREG1) can stimulate thermogenic fat formation, induce UCP1, and reduce diet‐induced obesity (DIO) in mice at normal room temperature. In this study, we investigated the effect of CREG1 administration and the importance of UCP1 in DIO inhibition under thermoneutral conditions at 30°C, which attenuate thermogenic fat formation. Interestingly, subcutaneous administration of recombinant CREG1 protein via an osmotic pump in C57BL/6J mice for four weeks increased UCP1 expression in interscapular brown adipose tissue (IBAT), inhibited visceral white fat hypertrophy with partial browning, and reduced DIO compared to that in PBS‐treated mice. The mRNA expression of energy metabolism‐related genes was significantly increased in the IBAT of CREG1‐treated mice compared to that in PBS‐treated mice. In contrast, adipocyte‐specific overexpression of CREG1 failed to improve DIO in UCP1‐knockout mice at thermoneutrality. Our results indicate the therapeutic potential of CREG1 administration for obesity under thermogenic fat‐attenuating conditions and highlight the indispensable role of UCP1 in the DIO‐inhibitory effect of CREG1. Abstract : Subcutaneous administration of recombinant CREG1 protein in C57BL/6J mice increased UCP1 expression in brown adipose tissue, inhibited visceral white fat hypertrophy, and reduced diet‐induced obesity (DIO) compared to that in PBS‐treated mice at thermoneutrality. In contrast, adipocyte‐specific overexpression of CREG1 failed to improve DIO in UCP1‐knockout mice. Our results indicate the therapeutic potential of CREG1 administration for obesity and highlight the indispensable role of UCP1 in the DIO‐inhibitory effect of CREG1.